Ce que la peur fait à l’engagement féministe - Blais, Mélissa (Lien social et Politiques, 2021)
Alors qu’on associe généralement la peur à des réflexes tels que la fuite, l’inhibition ou la démobilisation lorsqu’il est question de militantisme, cet article examine comment cette émotion peut parfois stimuler l’engagement de militantes féministes. Située au croisement des approches « actionnistes » (Bernard, 2017) des émotions, de la sociologie des mouvements sociaux et de la sociologie féministe, la discussion proposée s’inspire de 87 entretiens semi-dirigés réalisés entre 2006 et 2015 à travers le Québec, et d’une comparaison entre les milieux féministes suisses romands et québécois grâce aux 31 entretiens réalisés en 2018 et 2019 dans ces deux régions. En tenant compte des niveaux macro, méso et micro de l’analyse, l’article interroge les effets contrastés de la peur sur l’engagement féministe selon le positionnement des actrices dans les rapports sociaux de race, de classe et de sexualité, mais aussi selon les origines de la peur (intra ou extra mouvement), son degré d’intensité, ses interactions avec d’autres émotions (dont la colère) et le travail émotionnel (Hochschild, 2012) des féministes interrogées. L’article brosse ainsi un portrait des causes de la peur chez les féministes pour ensuite analyser les séquences émotionnelles les plus récurrentes en vue de mettre en relief diverses combinaisons émotionnelles et leurs effets sur l’engagement des féministes.
https://www.erudit.org/fr/revues/lsp/2021-n86-lsp06205/1079494ar/
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; discipline; europe; genève; militance; montréal; mouvements féministes; peur; périodes historiques; québec; racisme; rapports sociaux; ressource en ligne; régions géographiques; sciences humaines; sociologie; suisse romande; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences policières; émotions

Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0104-12902021000200202&tlng=pt
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Inhale exhale 2021 opener: Radical pleasure with Ericka Hart (2021)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; corps; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sex-positivity; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Une poupée en chocolat - Gay, Amandine (Les éditions du remue-ménage, 2021)
En mobilisant les outils de la sociologie, ce livre met à distance le discours moral ou humaniste sur l'adoption transraciale ou transnationale, afin d'aborder celles-ci d'un point de vue politique. Ces formes d'adoption sont en effet traversées par des enjeux qui vont au-delà de l'amour ou du désir d'enfant. Pour les comprendre, ce livre introduit une perspective théorique et militante encore trop peu connue en France : la justice reproductive, qui considère les disparités d'accès aux techniques reproductives, contraceptives, abortives et de stérilisation, ou encore les placements et les adoptions d'enfants, comme résultant d'inégalités systémiques. Le texte navigue entre un récit de vie poignant et des affiliations choisies aux théories critiques de la race, aux Cultural Studies, aux études féministes, aux études décoloniales et aux théories queer. Amandine Gay répond ainsi à l'urgence pour les personnes adoptées–et pour les autres–d'ouvrir un champ de réflexion, fondésur leurs expériences et expertises, analysant les rapports de pouvoir qui s'exercent dans l'adoption, et les structures conventionnelles de la parenté.
Section: 259 pages ; 20 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; antiracisme; approches et analyses; corps; cours; discipline; europe; france; féminisme décolonial; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques; écriture des femmes*

Les mots de trop - Les mots de trop (2021)
Les mots de trop est un outil de lutte et de sensibilisation à destination de tous·tes les étudiant·es des milieux de la culture.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; arts; belgique; capacitisme; discipline; france; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; suisse; système colonial; systèmes d'oppressions; thématiques; témoignages; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques